Effects of nitrogen quality and quantity on weed-crop competition - Hallberg, Lukas (2019)
The intensification of agricultural activities has provided unprecedented increases in crop production. In the light of this development concerns have been raised about its negative environmental impact. High-input farm management has further reduced the weed diversity and shaped weed communities to consist of a few highly competitive weed species. Ecological theory and soil microbial processes presents another perspective focusing on managing weeds with the use of different nutrient sources and crop diversity. The establishment of distinct resource pools in soil allow nutrients to be segregated between species and reduce weed-crop competition. The aim of this study was to investigate the influence of different nutrient sources in different quantities on competitive interactions between the weed species Avena fatua (wild oat) and Matricaria perforata (scentless chamomille) and the crop Avena sativa (oat) intercropped with the cover crop Trifolium resupinatum (Persian clover). The model plants were grown in a greenhouse in pots prepared with three soil substrates containing different nitrogen sources and quantities. A. fatua and A. sativa biomass and shoot height were statistically analysed in order to investigate the species responses to changes in nitrogen quality and quantity. A. sativa yield loss due to A. fatua competition were studied at four different A. fatua densities. The response to changes in soil nitrogen quality, nitrogen quantity and plant density were greater for A. sativa compared to A. fatua. Higher resource pool diversity increased the interspecific competition between A. fatua and A. sativa. The unresponsiveness of A. fatua to changing nutrient regimes and competition suggests that reinforced competition from the crop could be used to exhaust the weed’s energy reserves. Growth of T. resupinatum and M. perforata was insufficient to influence A. sativa in the experiment.